Summary report 1998-2002 (The Centre GeorgetownGY, 2003)
Summarizes the activities of the Iwokrama Centre over the period 1998 to 2002. Provides stakeholders with an understanding of the activities and direction of the Centre and programme in this period that forms the basis for the future activities of the Centre.
Bibliography: p. 36-40